Prison of the being: A contemporary problem - Macedo, Mônica (2009)
The article addresses the associative link between reason and the promise of happiness set in the illuminist ideology and questions their influence on the construction of the contemporary subject. Reflecting on the process of subjectivity and its impact in the field of otherness, it is proposed that the logical reason does not recover the truth of the subject. Psychoanalysis is presented as a key resource for reflection on the human suffering at present, given that the prevalence of diseases linked to narcissism reflects a kind of distancing of the subject inrelation to himself. Modernity, which waved opportunities for freedom emphasizing desire as a force of change, loses room to a postmodern culture that prioritizes having over being.